Pelatihan dan Pendampingan Informasi Geospasial Berbasis Sistem Informasi Geografi (SIG) dalam Meningkatkan Kompetensi Guru Geografi - Mohammad Lasaiba (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The rapid development of GIS geospatial information technology demands proficiency from geography teachers, but teachers tend to have minimal knowledge of the technology, and even the impression that teaching and learning activities are not being used optimally. I have. GIS geospatial information technology is very useful in describing environmental problems, metropolitan areas, floods, and various activities to establish trends, determine best locations, and identify patterns and models. The purpose of this activity is the enhancement and application of geographic information technology based on geographic information systems for geography teachers in the form of training and instruction, including data entry, management, analysis and presentation. In carrying out this activity, the participants, while receiving a strengthening of GIS concepts and GIS components, created maps of slopes, elevations and landslides in operational demonstration activities, then classified and scored them, and evaluated them. Click Overlay (Overlay) to create a new map with the new classification. The results of this activity show better control as well as higher enthusiasm and responsiveness during the training activity. The whole operation went smoothly. In addition, GIS education can enhance the effectiveness of geography education through application in schools.